THE IMPACT OF MANAGEMENT ON EMPLOYEE SATISFACTION IN HOSPITALITY ESTABLISHMENTS IN THE REPUBLIC OF SERBIA - Šmugović, Stefan; Ivanović, Velibor; Kalenjuk Pivarski, Bojana; Tešanović, Dragan; Vujasinović, Sofija (The Business of Tourism, 2025)
Employee satisfaction is one of the key factors influencing service quality in the hospitality industry, and the role of management in shaping it is of essential importance. The aim of this study is to examine the impact of managerial practices on employee satisfaction in hospitality establishments in the Republic of Serbia. The research is based on a survey conducted among 153 employees in various types of hospitality establishments. The results indicate that employees highly value teamwork and the opportunity to utilize their own skills, but there is room for improvement in the areas of communication transparency and managerial flexibility. This study contributes to a better understanding of the factors affecting employee satisfaction in the hospitality sector and can serve as a basis for improving managerial strategies aimed at enhancing the work environment and increasing employee satisfaction.
Keywords: management; hospitality; job satisfaction; Republic of Serbia